2023
DOI: 10.1111/1467-8489.12505
|View full text |Cite
|
Sign up to set email alerts
|

Public works programmes and agricultural risk: Evidence from India

Abstract: The agricultural sectors in many low‐ and middle‐income countries remain highly vulnerable to weather risk, a vulnerability that will only intensify under climate change. The globally trending public works programmes have the potential to impact weather‐related agricultural risk. I explore the impact of India's National Rural Employment Guarantee Act (NREGA) on weather‐related agricultural risk. My empirical strategy explores the staggered roll‐out of NREGA and random weather fluctuations. Using a nationwide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Calamitous weather, such as excessive precipitation during the crop‐growing and harvest seasons, has drawn considerable interest in the literature under the backdrop of climate change. An increasing amount of evidence has shown that the increased frequency of calamitous weather exposes crop production to more severe risks than changes in mean climate, negatively affecting crop yields and food security (McCarl et al., 2008; Taraz, 2023; Urban et al., 2015). Not only can calamitous weather during the growing season affect crop yields, but those during the harvest season can also adversely affect crop yields, especially when calamitous weather prevents timely harvest (Amonoo, 2013; Gobin, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calamitous weather, such as excessive precipitation during the crop‐growing and harvest seasons, has drawn considerable interest in the literature under the backdrop of climate change. An increasing amount of evidence has shown that the increased frequency of calamitous weather exposes crop production to more severe risks than changes in mean climate, negatively affecting crop yields and food security (McCarl et al., 2008; Taraz, 2023; Urban et al., 2015). Not only can calamitous weather during the growing season affect crop yields, but those during the harvest season can also adversely affect crop yields, especially when calamitous weather prevents timely harvest (Amonoo, 2013; Gobin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…exposes crop production to more severe risks than changes in mean climate, negatively affecting crop yields and food security (McCarl et al, 2008;Taraz, 2023;Urban et al, 2015). Not only can calamitous weather during the growing season affect crop yields, but those during the harvest season can also adversely affect crop yields, especially when calamitous weather prevents timely harvest (Amonoo, 2013;Gobin, 2018).…”
mentioning
confidence: 99%